2019
DOI: 10.35940/ijrte.b1189.0982s919
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Malaysian Exchange Rate Using Microstructure Fundamental and Commodities Prices: A Machine Learning Method

Abstract: The key objective of this research is to investigate the short run dynamics of the exchange rate using commodity prices and microstructure market variables for developing economies, Malaysia. The analysis of the literature revealed different school of thought where one claims the strong correlation among the variables while other significantly reject the relationship. There is mixed results that support and reject the accurate forecasting of the exchange rate through different determinants. Therefore, in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…This suggests that the application of the SVM algorithm is less fitting for the five Malaysian stocks used in the paper. Similarly, the recent paper by [20] stated that RF has higher accuracy than SVM in predicting asset prices on Malaysian commodities prices and microstructure market variables. It is also found that the effectiveness of the algorithm used depends on the size of the dataset of the study.…”
Section: B Related Workmentioning
confidence: 98%
“…This suggests that the application of the SVM algorithm is less fitting for the five Malaysian stocks used in the paper. Similarly, the recent paper by [20] stated that RF has higher accuracy than SVM in predicting asset prices on Malaysian commodities prices and microstructure market variables. It is also found that the effectiveness of the algorithm used depends on the size of the dataset of the study.…”
Section: B Related Workmentioning
confidence: 98%